Reinstatement and lectotypification of Phyllanthus rosellus (Phyllanthaceae), an endemic species from the state of Minas Gerais, Brazil - Torres, Alícia Marques; Da Silva, Marcos José (Phytotaxa, 2024)
Phyllanthus rosellus, an endemic species from the state of Minas Gerais, Brazil, was treated under Phyllanthus niruri subsp. lathyroides. After analyzing herbarium collections, including all types related to the names P. niruri and P. rosellus, we conclude that both species are morphologically distinguishable, and consequently we propose the reinstatement of P. rosellus. Additionally, as the latter is a species usually known from literature dating from the 19th century, where its description overlaps with that of some congeners, we provide its description, illustrations, preliminary conservation status, images in their habitat, as well as designate a lectotype for it.